1990
DOI: 10.1111/j.2044-8341.1990.tb01617.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's anticipation and experience of childbirth: The independence of fulfilment, unpleasantness and pain

Abstract: Adjectives or phrases used by women in their description of childbirth were identified by interviewing two groups of 10 women, one drawn from an antenatal clinic, the other following delivery of a healthy child. The terms obtained were formed into a questionnaire on which 106 antenatal women described their expectations of childbirth and 82 postnatal women described their experience. Principal components analysis revealed two important findings. First, the ratings were multidimensional; that is, a dimension of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
4

Year Published

1992
1992
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 6 publications
1
43
0
4
Order By: Relevance
“…Indeed, women's perception of pain during childbirth has been found to be unrelated to how they assess the experience as a whole, which can even be seen to be pleasurable or erotic (Bergum, 1989;Lundgren & Dahlberg, 1998;Niven, 1988;Rabuzzi, 1994;Salmon, Miller, & Drew, 1990;Waldenström, Bergman, & Vasell, 1996). Labour is therefore an internal experience and part of that experience is that the woman's body functions outside her control (England & Horowitz, 1998;Lundgren & Dahlberg, 1998;Simkin, 1992).…”
Section: Childbirth: Feeling Out Of Controlmentioning
confidence: 99%
“…Indeed, women's perception of pain during childbirth has been found to be unrelated to how they assess the experience as a whole, which can even be seen to be pleasurable or erotic (Bergum, 1989;Lundgren & Dahlberg, 1998;Niven, 1988;Rabuzzi, 1994;Salmon, Miller, & Drew, 1990;Waldenström, Bergman, & Vasell, 1996). Labour is therefore an internal experience and part of that experience is that the woman's body functions outside her control (England & Horowitz, 1998;Lundgren & Dahlberg, 1998;Simkin, 1992).…”
Section: Childbirth: Feeling Out Of Controlmentioning
confidence: 99%
“…Fathers were contacted between 48 hours and 6 days after the baby's birth. The Experience of Childbirth questionnaire (Salmon & Drew, 1992;Salmon, Drew, & Miller, 1990), the Miller Behavioral Style Scale (Miller, 1987), and the Edinburgh Postnatal Depression Scale (Cox, Holden, & Sagovsky, 1987) were given to participants while they were still on the postnatal unit and again 6 weeks later. Greenhalgh et al (2000) discovered that fathers use blunting (avoidance of the anxiety-producing situation), monitoring (a form of seeking information and responding with action), or a combination of both as coping techniques.…”
Section: Key Paternal Childbirth Fearsmentioning
confidence: 99%
“…Pain is associated with a negative experience (Séguin et al 1989, Waldenström 1999, Mackey 1998, and post-partum mood (Reading & Cox 1985). On the other hand, Salmon et al (1990) found that the degree of pain could not alone define or exhaust the experience of childbirth. The complexities of pain during labour have been described by Waldenström et al (1996) Even if pain during childbirth is characterised as a very severe pain (Melzack 1993, Niven & Gijsbers 1984 it is not described as an entirely negative experience (Waldenström et al 1996).…”
Section: Ideas On Pregnancy and Childbirth Todaymentioning
confidence: 95%